Impact of SGLT2 inhibitors treatment on the chronic kidney disease in people with type 2 diabetes - Marcin Czarkowski; Karolina Raksa; Ewelina Powroźniak; Karol Spozowski (Kazimierz Wielki University, 2022)
Diabetes is the most common cause of CKD (chronic kidney disease). CKD is also one of the most important diabetic complication. SGLT2 (sodium glucose co‐transporter‐2) inhibitors are new class of medication used to lower high blood glucose level in people with type 2 diabetes. In new researches SGLT2 inhibitors demonstrated a significant and clinically relevant reduction in the risks of albuminuria and progression of nephropathy, doubling of serum creatinine levels, and initiation of renal replacement therapy. This review focuses on the therapeutic effectiveness of using SGLT2 inhibitors for the treatment of CKD in type 2 diabetes.